Implementation of a discrete-event control system using LabVIEW - Tiu, Chee King. (2008)
The LLD has been used to program a palletizing system available in the Design Lab of School of EEE, NTU. It has clearly demonstrated the shortcomings of LLD as mention above. For this project, we designed and modeled the control sequence using a structured programming language that does not suffer from the above mentioned weakness. State machine was used in this project to represent all the state of the palletizing system sequence as well as serving as reference for the programming of control system. In this project, Lab VIEW programming is used to program the palletizing system.